Ensuring the reliability of corrosion and mechanical resistance of pipelines and steel structures of oil and gas complexes - Zyma, Oleksandr; Steblianko, Valeriia; Pahomov, Roman; Mytrofanov , Pavlo (Academic journal Industrial Machine Building Civil Engineering, 2023)
The article addresses the issue of ensuring the reliability and durability of steel structures used in oil and gas complexes. Attention is drawn to the need for research and improvement of scientific, technical, and technological developments in the field of corrosion-mechanical resistance of metal structures. The article describes the results of experimental research aimed at analyzing the causes and mechanisms of metal strength loss during operation, and proposes a method for predicting the residual working life of structures. The obtained results make a significant contribution to the development of technical and design measures to enhance the efficiency and reliability of oil and gas complexes